2022
DOI: 10.1002/sd.2395
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable development and stakeholder engagement in the agri‐food sector: Exploring the nexus between biodiversity conservation and information technology

Abstract: Organizations across various industries engage in biodiversity conservation as a way to achieve sustainable development and to manage stakeholder engagement expectations. Although the importance of information and communication technology to promote biodiversity conservation has been recognized, little attention has been

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 109 publications
0
5
0
Order By: Relevance
“…An exploratory empirical study was planned based on a qualitative in‐depth analysis of sustainability reports. The descriptive information included in the sustainability reports was analyzed using a process of systematic categorization that groups information around recurring concepts and issues (Aké & Boiral, 2022; Schreier, 2012), following these general steps (see Figure 1): (1) data extraction phase; (2) organizing phase; (3) reporting results phase.…”
Section: Methodsmentioning
confidence: 99%
“…An exploratory empirical study was planned based on a qualitative in‐depth analysis of sustainability reports. The descriptive information included in the sustainability reports was analyzed using a process of systematic categorization that groups information around recurring concepts and issues (Aké & Boiral, 2022; Schreier, 2012), following these general steps (see Figure 1): (1) data extraction phase; (2) organizing phase; (3) reporting results phase.…”
Section: Methodsmentioning
confidence: 99%
“…Over the past 30 years, most terrestrial ecosystems in Africa have experienced large biodiversity losses. Conversion of natural ecosystems into agricultural lands and urban areas is the main cause of these losses (Aké & Boiral, 2022). CC exacerbates biodiversity loss and could result in significant losses of plant species, as well as over half of some bird and mammal species in the region (IPBES, 2018).…”
Section: Changes In Ecosystem Conditionmentioning
confidence: 99%
“…For example, a recent report by Crippa et al (2021) showed that the food system is responsible for 34% of the total greenhouse gas (GHG) emissions globally. As such, firms are subject to strong pressure from various stakeholders to take responsibility for their actions, possibly not only enhancing their reputation and economic performance (ECOP) but also reducing their environmental footprint (Aké, et al, 2023; Grimm et al, 2014; Luque‐Vílchez et al, 2023). For instance, in 2015, the reputation of firms such as Cargill, Tyson, and Yara suffered because of their contributions to climate impact (Levitt, 2015).…”
Section: Introductionmentioning
confidence: 99%